The most wonderful time [large type] - Michaels, Fern; Finz, Stacy; Title, Sarah; McCoy, Shirlee (Wheeler Publishing, A part of Gale, Cengage Learning, 2016)
What goes better with mistletoe and merriment than four short stories about the sweet beginning of romance?